2011
DOI: 10.1063/1.3596818
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent magnetic moments in ultrafine diamagnetic systems

Abstract: Theory of magnetic fluid heating with an alternating magnetic field with temperature dependent materials properties for self-regulated heating Recently, unusual magnetic properties were found experimentally in otherwise diamagnetic nanoparticles. Our experiments and analysis revealed that a universal expression can describe the size-dependent magnetic moments in ultrafine diamagnetic systems, including Au, Pd, and HfO 2 nanoparticles. A model was presented to explain the observed phenomenon. It suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Moreover, an external magnetic field can be conveniently applied to a reaction system. It is reported that the magnetic susceptibility of small nanoparticles changes rapidly with particle size. , Therefore, the applied external magnetic field will inevitably affect the motion of magnetic nanoparticles, whose size still changes during chemical synthesis. If the applied magnetic field changes, the force exerted by the field on each magnetic particle is proportional to the magnetic moment of the particle, which is related to its size.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an external magnetic field can be conveniently applied to a reaction system. It is reported that the magnetic susceptibility of small nanoparticles changes rapidly with particle size. , Therefore, the applied external magnetic field will inevitably affect the motion of magnetic nanoparticles, whose size still changes during chemical synthesis. If the applied magnetic field changes, the force exerted by the field on each magnetic particle is proportional to the magnetic moment of the particle, which is related to its size.…”
Section: Introductionmentioning
confidence: 99%